ICT and environmental sustainability: Any differences in developing countries?. (15th May 2021) - N'dri, Lasme Mathieu; Islam, Moinul; Kakinaka, Makoto
Abstract: To achieve the Sustainable Development Goals (SDGs), governments have committed to promote policies towards a sustainable environment regarding the main determinants of carbon dioxide (CO2 ) emissions. Focusing on the importance of the information and communication technology (ICT) on sustainable environment, this study identifies the long-run relationship between ICT and CO2 emissions in developing countries. This study uses a panel pooled mean group autoregressive distributive lag (PMG-ARDL) model for 58 developing nations from 1990 to 2014. This analysis clearly shows that the use of ICT is environmentally favorable for relatively low-income developing countries, while no evident relationship exists for relatively high-income developing countries. To achieve environmental sustainability, ICT policies need to be more emphasized to mitigate environmental problems in least-developed countries.